Utilization of deep learning for the implementation of pancasila philosophy in pancasila education in christian middle schools - Suryo Ediyono; Dwi Septiwiharti; Riko Andarista (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study investigates the potential of a deep learning pedagogical approach to significantly improve how Pancasila Philosophy is implemented and understood within the Pancasila Education curriculum at a Christian Junior High School in Surakarta, Central Java, Indonesia. Recognizing the importance of Pancasila in shaping Indonesia's national identity and character, this study explores the design, implementation, and evaluation of a specific deep learning intervention. This intervention was carefully tailored to fit the unique educational context of a Christian junior high school setting, taking into account the integration of faith-based values and the nuances of Indonesia's local cultural landscape. This study seeks to determine the effectiveness of this deep learning strategy in fostering not just a superficial understanding, but a deep and internalized understanding of the core principles of Pancasila among students. By analyzing student engagement, levels of understanding, and attitude changes, the findings aim to provide valuable insights for educators and policymakers. Ultimately, this study seeks to contribute to the development of a more impactful pedagogical model that can strengthen the integration of Pancasila Philosophy across secondary education in Indonesia, particularly within the unique opportunities and constraints presented by faith-based learning environments.